Предмет: Алгебра,
автор: NikaVolk80
1. (1-2х)^2=(2х-3)(2х+3)-5
2. (х+4)^2=7х+(х-3)^2
Помогите решить, очень нужно, заранее огромное спасибо
Ответы
Автор ответа:
0
(1-2х)²=(2х-3)(2х+3)-5
1-4x+4x²=4x²-9-5
1-4x=-14
4x=15
x=3,75
(х+4)²=7х+(х-3)²
x²+8x+16=7x+x²-6x+9
8x+16=x+9
7x= -7
x= -1
1-4x+4x²=4x²-9-5
1-4x=-14
4x=15
x=3,75
(х+4)²=7х+(х-3)²
x²+8x+16=7x+x²-6x+9
8x+16=x+9
7x= -7
x= -1
Похожие вопросы
Предмет: Русский язык,
автор: whatever24
Предмет: Химия,
автор: andriyko72
Предмет: Алгебра,
автор: asocialperson
Предмет: Математика,
автор: Аноним
Предмет: Экономика,
автор: галя11111